Accuracy of anthropometric-based predictive equations for tracking fat mass over a competitive season in elite female soccer players: a validation study - Baroncini, G.; Campa, F.; Tarabini, P. C.; Sala, A.; Boldrini, L.; Mazzoni, S.; Paoli, A. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background and aims Body fat is a key body composition parameter monitored in soccer. Identifying reliable alternatives to laboratory techniques for assessing body fat during the competitive period is essential. This study aimed to evaluate the cross-sectional and longitudinal validity of anthropometric prediction equations in elite female soccer players.